Health-related quality of life scores of ultralow rectal cancer patients after conformal sphincter preservation operation compared to newly derived preoperative EORTC QLQ-C30, CR38 reference values and EORTC QLQ-C30 norm - Ding, Hai‐bo; Sun, Ge; Yu, Guan‐yu; Gao, Xian‐hua; Lou, Zheng; Kuo, Zheng; Gong, Hai‐feng; Zhu, Xiao‐ming; Zhang, Wei (Frontiers in Oncology, 2026)
BackgroundPostoperative quality of life (Post-QoL) is the key to measuring the effectiveness of sphincter-preserving operation such as Conformal sphincter preservation operation (CSPO) for ultralow rectal cancer. This study aimed to establish preoperative QoL (Pre-QoL) reference values for rectal cancer patients and compare them with post-CSPO QoL to highlight CSPO's benefits in preserving QoL.MethodsClinical baseline data and Post-QoL data (EORTC QLQ-C30, CR38) from ultralow rectal cancer patients who underwent CSPO at Shanghai Changhai Hospital from August 2011 to April 2020 were retrospectively collected, and Pre-QoL reference values for rectal cancer patients were extracted through a literature review. The Post-QoL of CSPO were compared with the newly derived Pre-QoL reference values and the norm in the EORTC QLQ-C30 reference value manual.ResultsCompared with the newly derived preoperative C30 reference value, the preoperative C30 norm for colorectal cancer (CRC) and the general population, the Post-QoL of CSPO can exceed the preoperative level and reach a similar level to general population. Compared with the gender, and stage subgroups of the preoperative C30 norm for CRC, the Post-QoL of CSPO showed that male patients benefited more, while patients stage III-IV had limited benefits compared to other subgroups. Compared with the newly derived preoperative CR38 reference value, the Post-QoL of CSPO is comparable to that before surgery, but the sexual function and sexual enjoyment dimensions are significantly lower than those before surgery.ConclusionsThe Long-term QoL after CSPO can exceed the preoperative level and reach a similar level to general population. However, postoperative diarrhea symptoms and decreased sexual function and enjoyment should be taken seriously and measures should be actively taken to promote recovery. Patients stage III-IV had limited benefits compared to other subgroups, and the selection and surgical procedures need to be more cautious.